The Effect of Five-Finger Hypnosis Relaxation Educational Videos as Psychosocial Support on Reducing Anxiety Levels in Student Chronotype during Distance Learning during the COVID-19 Pandemic - Rully Annisa; Marta Tania Gabriel Ching Cing (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Distance learning is currently a medium and learning resource that maximizes modern internet-based technology and communication and is carried out online and focuses on individuals or groups and student activities remotely without face-to-face, the interaction of material delivery and assignments is completely done online. Students' activities in distance learning currently require that normal sleeping hours be switched to doing many tasks. The term is also known as chronotype, and it refers to a variety of human control over biological circadian rhythms that include the morning, night, and intermediate types. However, not all students are prepared to participate in distance learning. Students' perceptions of distance learning during an uncertain period of time cause fatigue, stress, or anxiety. The purpose of this study was to determine the effect of using five-finger hypnosis relaxation educational videos on decreasing anxiety levels in the chronotype of students. Design: Pre-Experimental Design Type One Group Pretest-Posttest Methdos: The method used in this study is a pre-experiment design ypene-group pretest-posttest. The total number of respondents was 37 students who were during distance learning using the simple random sampling technique. Data collection used a questionnaire of The Zung Self-Rating Anxiety Scale was used to measure anxiety levels before and after the intervention, and the Morningness-Eveningness Questionnaire was used to determine the type chronotype (MEQ). Data analysis using Paired Sample T Test. Results: The results of statistical tests showed the majority of respondents (64.9 %) experienced mild anxiety prior to receiving the intervention, while 1 student experienced severe anxiety (2.%5). Furthermore, after receiving the intervention, the majority of the respondents experienced mild anxiety, with as many as 26 students (70.3 %) no longer experiencing severe anxiety.  The intervention group has a positive mean difference in Anxiety Levels of 1.36, indicating that there is a tendency to decrease anxiety levels after the intervention with an average decrease of 1.36. Based on the p-value = 0.011, it can be concluded that there is a significant difference in the anxiety level of the intervention group before and after the intervention (where p 0.05) with a t count = 2.689 (t count > t table (df 36 = 1.687094) with a positive value (+) indicates that the anxiety level score before the intervention is higher than the anxiety level score after the intervention. This means that the five finger hypnosis technique intervention is in reducing anxiety levels. Conclusions: Five finger hypnosis therapy with video by providing comfort and relaxation is very effective for reducing anxiety levels. This activity is also intended to divert attention and can lower blood pressure, breathing, the tension in the muscles, metabolic rate, and pulse.